Oblicz jak najprosciej:
a) (-4,2) x 6,8 + (-4,2) x 3,2
b) (-5,6) x 8,4 + (-5,6) x 1,6
c) 7,2 x (-1,2) - (-1,2) x 3,1
*d) 11 x (-2,7) - 11 x (-4,8)
*e) (-3,7) x 2,4 -3,5 x (-3,7)
*f) (-7,5) x (-3,3) - (-7,5) x 8

Bardzo bym prosil byscie sie rozpisywali a nie podawali tylko wynikow.

3

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-18T20:00:29+01:00
A) (-4,2) x 6,8 + (-4,2) x 3,2=(-4,2)(6,8+3,2)=(-4,2)*10=-42
b) (-5,6) x 8,4 + (-5,6) x 1,6=(-5,6) ( 8,4 + 1,6)=(-5,6)*10=-56
c) 7,2 x (-1,2) - (-1,2) x 3,1= (-1,2)(7,2 - 3,1)=(-1,2)*4,1=-4,92
*d) 11 x (-2,7) - 11 x (-4,8)= 11(-2,7-(-4,8))=11(-2,7+4,8)=11*2,1=23,1
*e) (-3,7) x 2,4 -3,5 x (-3,7)=(-3,7)(2,4 -3,5 )=(-3,7)*(-1,1)=4,07
*f) (-7,5) x (-3,3) - (-7,5) x 8=(-7,5)[ (-3,3) - 8]=(-7,5)*(-11,3)=84,75
1 5 1
2009-11-18T22:19:36+01:00
A)=(-42/10)*68/10+(-42/10)*32/10=-714/25-336/25=-1050/25=-42
b)=(-56/10)*84/10+(-56/10)*16/10=-1179/25-224/25=-1400/25=-56
c)=72/10*(*12/10)-(-12/10)*31/10=-216/25+186/50=-432/50+186/50=-246/50
d)=11/1*(-27/10)-11/1*(-48/10)=-297/10+528/10=231/10
e)=(-37/10)*24/10-35/10*(-37/10)=-888/100+1295/100=407/100
f)=-75/10*(-33/10)-(-75/10)*8=2475/100+600/10=2475/100+6000/100=8475/100
2009-11-18T22:37:10+01:00
A) (-4,2) x 6,8 + (-4,2) x 3,2=(-4,2)(6,8+3,2)=(-4,2)*10=-42
b) (-5,6) x 8,4 + (-5,6) x 1,6=(-5,6) ( 8,4 + 1,6)=(-5,6)*10=-56
c) 7,2 x (-1,2) - (-1,2) x 3,1= (-1,2)(7,2 - 3,1)=(-1,2)*4,1=-4,92
*d) 11 x (-2,7) - 11 x (-4,8)= 11(-2,7-(-4,8))=11(-2,7+4,8)=11*2,1=23,1
*e) (-3,7) x 2,4 -3,5 x (-3,7)=(-3,7)(2,4 -3,5 )=(-3,7)*(-1,1)=4,07
*f) (-7,5) x (-3,3) - (-7,5) x 8=(-7,5)[ (-3,3) - 8]=(-7,5)*(-11,3)=84,75